Pengaruh Partisipasi Eksekutif Terhadap Pengembangan Teknologi Informasi UMKM Di Surakarta - Hernawati Pramesti; Mujiyono (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2025)
The development of IT (Information Technology) management is influenced by the involvement of owners, owner participation, owner background, and company conditions, this is a factor that affects the progress of IT management. The purpose of this study is to find out: Owner participation factors affect the progress of IT management in MSMEs in Surakarta. The ownership involvement factor affects the progress of IT management in MSMEs in Surakarta. The condition of the owner's organization affects the progress of IT management in MSMEs in Surakarta. The owner's background factor affects the progress of IT management in MSMEs in Surakarta. The factors of participation, involvement, conditions, and background of the owner affect the progress of IT management in MSMEs in Surakarta. The MSME research population in Surakarta is 40 MSMEs. Data was collected through questionnaires. Data analysis used t-test and F-test techniques. The conclusions of the research results are: (1) The variable of owner participation is proven to have no influence on the variable of information technology development. (2) The variables of owner involvement affect the variables of information technology development. (3) The variables of organizational conditions have no effect on the variables of information technology development. (4) The background variable of the owner has no effect on the variable of information technology development. (5) The results of the independent variables together have no effect on the dependent variables